2016
DOI: 10.1186/s12916-016-0673-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of serious infections with immunosuppressive drugs and glucocorticoids for lupus nephritis: a systematic review and network meta-analysis

Abstract: BackgroundTo perform a systematic review and network meta-analysis (NMA) to compare the risk of serious infections with immunosuppressive medications and glucocorticoids in lupus nephritis.MethodsA trained librarian performed two searches: (1) PubMed for all lupus nephritis trials from the end dates for the systematic review for the 2012 American College of Rheumatology (ACR) lupus nephritis treatment guidelines and the 2012 Cochrane Systematic Review on treatments for lupus nephritis, to September 2013; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 40 publications
6
86
1
4
Order By: Relevance
“…Previous studies showed disease activity,high anti‐dsDNA titers, low complement levels, nephritis, leucopenia, GC doses and immunosuppressants were risk factors for infections in lupus patients . A nationwide cohort of SLE patients showed that male sex and Black race were risks factors for infection, whereas hydroxychloroquine was a protective factor …”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed disease activity,high anti‐dsDNA titers, low complement levels, nephritis, leucopenia, GC doses and immunosuppressants were risk factors for infections in lupus patients . A nationwide cohort of SLE patients showed that male sex and Black race were risks factors for infection, whereas hydroxychloroquine was a protective factor …”
Section: Discussionmentioning
confidence: 97%
“…Our data at the least suggest that the use of TAC is not inferior to conventional treatment. Moreover, we and others27 28 32 showed that the safety profile of TAC is very good in LN. Therefore, we would recommend TAC to be considered as a treatment option in patients with refractory LN.…”
Section: Discussionmentioning
confidence: 73%
“…The high frequency of functional bloating found in our SLE patients was also reported in an Asian study among patients with rheumatic disorders . Another potential explanation for the higher frequency of FGIDs in SLE patients may be that these patients may be immunosuppressed, which could predispose them to enteric infections . The role of gastrointestinal infections as trigger factors for postinfection disorders such as IBS has been described .…”
Section: Discussionmentioning
confidence: 99%